The importance of the protagonism of children and young people in Residential Care: A case study portuguese - Gaspar , João Pedro; Baptista, Rachel; Coelho , José António; Zamora, Maria Helena (Seven Editora, 2024)
The PAJE Platform – Support for (Ex)sheltered Youth – Association carried out a project supported by Eurochild that involved eight Residential Shelters for children and young people at risk, in the Central region of Portugal, with the aim of giving a voice to users of the Residential Care system in Portugal, placing them in the place of social protagonism. A case study research was carried out where one hundred people between twelve and twenty-two years old, institutionalized during a period of one to ten years, were interviewed. The data were collected through residents’ assemblies, without the presence of technicians or educators from the Shelters, and analyzed based on the content analysis methodology. The results revealed the importance of the reconstruction of plots, the rescue of identity and new possibilities of personal narratives of boys and girls. It is concluded that it is necessary to continue this type of work so that new public policies can be subsidized and rethink the way of serving this public. DOI:https://doi.org/10.56238/sevened2024.007-034